The Development of Student's Worksheet based on Scientific Approach on Matrix Material in High School - Nazli Andriani (Indonesian Journal of Education and Mathematical Science, 2022)
The formulation of the problem from this research was "Is the development of LKPD based on a scientific approach on matrix material in high school feasible to use? How do students respond to LKPD based on a scientific approach to matrix material?" The purpose of this study is to find out whether the development of LKPD based on a scientific approach to matrix material in high school is feasible to use. This research was a research and development that used a 4D development model which consists of 4 stages, such as the definition stage, the design stage, the development stage, and the dissemination stage. However, in this study, the researchers only limited it to the 3D stage, which was defining, designing and developing. The instrument in this study was a questionnaire sheet for the expert feasibility test. Based on the validation results from the validator, the student's worksheet assessment scores were obtained by two expert lecturers and one mathematics teacher with an average percentage value of 79% and categorized as "Eligible". For student responses to LKPD based on a scientific approach to the matrix material, the average percentage value is 86% and is categorized as "Very Good". It can be concluded that the LKPD based on a scientific approach to the matrix material developed by the researcher is feasible to be used as additional teaching material for students.